Description of Learning Climate in the 3 In 1 Training Program for Making Head Pin Embroideries - Desi Fitrianti; Ismaniar Ismaniar (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2019)
This research is motivated by the success of the 3 in 1 education and training program for making pinhead embroideries carried out by the Padang Industrial Training Center. This is allegedly due to the learning climate that occurred in the implementation of the program. This study aims to determine the description of the learning climate in the 3 in 1 training program for making pinhead embroideries held in Padang Biri-Birik, North Pariaman. This type of research is quantitative descriptive research. The population of this study was all of the 3 in 1 training participants making pinhead embroideries carried out by the Padang Industrial Training Center in 2019 totaling 70 training participants. The sample in this study amounted to 30 people. Data collection techniques using a questionnaire with a tool in the form of a statement list, while data analysis techniques use the percentage calculation. The results of the study show that the learning climate in the 3 in 1 Education and Training program for making pinhead stitches is seen from 1) the aspect of the physical environment is quite good. This was also illustrated by the participants' responses which became a sample dominated by always and frequently answered answers (93.35%), 2) in the aspect of the social environment also looked quite good. This is illustrated from the training participants' answers which became the most sampled answers that always and often reached (92.5%). The suggestion put forward in this research is to the management of the Central Indonesian Education and Training Center who carry out the 3 in 1 education and training program to make the pinhead embroidery so as to always maintain the learning climate for other upcoming training activities.Keywords: Learning Climate, Success